PEMANFAATAN SAMBILOTO UNTUK MENINGKATKAN IMUNITAS TUBUH PEKERJA INDUSTRI PARIWISATA INDONESIA DI MASA PANDEMI COVID-19 - Nila Rifai (Bogor Hospitality Journal, 2021)
In 2020 is a difficult time for tourism industries in the world due to the Covid-19 pandemic. No exception to the condition of Indonesian tourism which contracted quite deeply, where there was a decrease in foreign tourists to Indonesia compared to the previous year. Based on BPS data in 2020, foreign tourist visits to Indonesia were only around 4.02 million people, decrease by 75.03% compared to 2019 which amounted to 16.11 million people. There are many strategies taken by tourism industry players to attract tourists, including adapting new habits during the Covid-19 Pandemic and improving body immunity of tourism industry workers by consuming healthy foods and supplement products derived from Indonesian herbal plants. The purpose of this paper is to provide information about the benefits of Sambiloto to increase body immunity for workers in the tourism industry.The method used in this paper is literature study. The results showed that a herbal plant that could be used to improve body immunity during the Covid-19 pandemic is Andrographis paniculata. Based on empirical dan scientific evidence, These herbal plant have properties, including as an immunomodulator, anti-tuberculosis, antivirus, anti-inflammatory and antioxidant which can be used as a prevention of Covid-19 transmission.